The Teacher's Role in Forming Character of Care for the Environment and Student Discipline - Pohan, Mukmin; Dewi, Susi Fitria; Montessori, Maria; Putra, Eka Vidya (Jurnal Penelitian Pendidikan IPA, 2024)
The school has an education system designed to suit the needs of the times, one of which is character education, in character education there is the value of disciplined character. Students need to have a disciplined character so that positive values emerge in their daily activities This research aims to describe the role of teachers in forming students ' environmentally caring character and discipline through themes. The method used is qualitative with a phenomenological approach. At Seluan Island 1 Middle School. From the research results, it can be concluded that the role of teachers in forming disciplined character through environmental care activities at Seluan Island 1 Middle School, there are regular face-to-face meetings from 14.00 to 17.00, through environmental care activities carried out with a block model, namely by motivating continuously, then a regular model, namely, Saturday and Sunday Camps, Routine Training, Nature Exploration, and Ramu, Raft and Terap Inauguration so that it can transform students' disciplined attitudes through several physical, mental and skills activities through activities which were at the Saturday and Sunday camp held at SMP Negeri 1 Seluan Island. Because these activities can provide students with provisions ranging from knowledge to skills to shape their mental and character.